Use of functional magnetic resonance imaging in patients with irritable bowel syndrome and functional dyspepsia - Katarzyna Skrobisz; Grażyna Piotrowicz; Adrianna Drozdowska; Karolina Markiet; Agnieszka Sabisz; Patrycja Naumczyk; Grażyna Rydzewska; Edyta Szurowska (Gastroenterology Review)
Functional brain imaging (positron emission tomography – PET, functional magnetic resonance imaging – fMRI), allowing in vivo analysis of the brain-digestive tract interaction and the neurological mechanisms underlying visceral hypersensitivity, significantly advanced research and helped in the understanding of the interrelations in this field. Differences in this parameter can result from alterations in task-related cognitive states or from resting state processes. Nowadays, advanced imaging techniques such as fMRI are more frequently used and are acknowledged among both clinicians and radiologists in the diagnostic algorithm of digestive tract diseases. Functional dyspepsia is a condition in which neuroimaging allows for analysis of dysfunctions within the brain-gut axis (BGA) engaged in processing of visceral discomfort and pain. The results of studies in patient groups with irritable bowel syndrome prove that psychosocial factors significantly affect the mechanisms regulating visceral sensitivity within the brain. The BGA includes neuronal pathways (autonomic nervous system), neuroendocrine (hypothalamo-pituitary-adrenal axis), and neuroimmunological ones. Psychological processes affect the functioning of the digestive system and can cause dyspeptic symptoms. A patient’s mental condition associated with stress can affect processes taking place in the central nervous system and trigger somatic reactions in the digestive tract through the autonomic visceral system.